Large lung bullae in sarcoidosis. Issue 10 (October 1986) - Packe, G E; Ayres, J G; Citron, K M; Stableforth, D E
Abstract : Large lung bullae are a rare manifestation of pulmonary sarcoidosis. Of three patients with this complication, all had pulmonary infiltrates at presentation and two had bilateral hilar adenopathy. Hypercalcaemia developed during the course of the illness in all three patients. In each case the bullae had developed within four years of the diagnosis of sarcoidosis. In one woman a bulla resolved almost completely after it had become infected.